Direct sales and its impact on Automotive distribution - Belinger, Jan; Král, Petr, 1979-; Müller, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This masters thesis aims to explore the possible implementation of the direct distribution model within the automotive industry. The goal is to outline the possible distribution strategy, using the direct distribution model, for an auto manufacturer. The theoretical background and cases that are used to describe the practical usage of the model are based on a secondary research. More specific aspects of the distribution model are then based on interviews conducted with professionals from the automotive industry. The proposed distribution strategy consists of combination of several direct distribution models. Different models are used due to the distinct nature of the products, considered in the process of new distribution model design. The implementation would allow the OEM to gain more control over the distribution process and create more efficient distribution system.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses